1987
DOI: 10.1111/j.1529-8817.1987.tb04443.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARATIVE ULTRASTRUCTURE OF THREE SPECIES OF CHLOROSARCINA (CHLOROSARCINACEAE, CHLOROPHYTA)1,2

Abstract: Ultrastructural studies revealed that Chlorosarcina stigmatica Deason differs from C. brevispinosa and C. longispinosa Chantanachat and Bold because the vegetative cells possess a pyrenoid, and the zoospores have chlorophycean characteristics. Zoospores of the latter species exhibit pleurastrophycean characteristics including counterclockwise absolute orientation of the flagellar apparatus components. Nuclear division in C. longispinosa, like that of Friedmannia israelensis Chantanachat and Bold, is metacentri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…1, the investigated strains formed a highly supported lineage within the Trebouxiophyceae. Our study confirmed the separation of C. brevispinosa and C. longispinosa from other species of Chlorosarcina based on ultrastructural features (Deason and Floyd 1987), which Sluiman and Blommers (1990) have used for the establishment of Pleurastrosarcina . However, Sluiman and Blommers (1990) assigned this genus to the Ulvophyceae, because the Trebouxiophyceae was later described by Friedl (1995).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…1, the investigated strains formed a highly supported lineage within the Trebouxiophyceae. Our study confirmed the separation of C. brevispinosa and C. longispinosa from other species of Chlorosarcina based on ultrastructural features (Deason and Floyd 1987), which Sluiman and Blommers (1990) have used for the establishment of Pleurastrosarcina . However, Sluiman and Blommers (1990) assigned this genus to the Ulvophyceae, because the Trebouxiophyceae was later described by Friedl (1995).…”
Section: Discussionsupporting
confidence: 84%
“…How difficult the identification of taxa with this morphology is, can be demonstrated on the example of Chlorosarcina stigmatica . This species was described by Deason (1959) and the ultrastructure of the type strain (UTEX 962) was investigated by Deason and Floyd (1987). Two other strains were isolated by Schwarz (1975) and Trenkwalder (1975), ASIB S163 and ASIB T105, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations